A Computational Study Of Flexibelity And Vibration Analysis In Tire And Road Using Ansys Software 17.2 - Rima Melati Tanjung (Institute of Computer Science (IOCS), 2020)
The use of the car as a means of driving, Comfort, safety, and performance is the goal of the car design parameters. Tires are an important part that greatly affects the stability and performance of the vehicle. Because the tire is the only part of the vehicle that is directly related to the road surface. Both of them must be integrated to each other to get comfort, and good performance and safe when driving. Computerized simulation of mechanical dynamics is a useful tool to understand various processes of the occur on tires and roads. The simulation is conducted on radial tire type 195 / R 7514 tread block pattern and asphalt material as the path of road surface at the condition of car speeding with speed 0-50 km/h. Simulation condition is limited on constant loading, and the air pressure in the tire variation 28 Psi, 30 Psi, 32 Psi, 34 Psi, and 36 psi. Simulation data, the value of deflection and vibration is the biggest factor of damage and wear of tires and roads. And 30 Psi is the most appropriate tire pressure.